Bequeme Preise im Quickservice-Bereich; Convenient Prices in the Quick Service Sector - Anke Mos̈er; Laura Kriep (German Journal of Agricultural Economics (GJAE), 2014)
– Due to changes in demographic and social circumstances, the importance of food-away-from-home consumption increases. However, detailed facts on pricing strategies in this sector are still missing in Germany. This paper aims to provide cross-sectional evidence of pricing strategies in the quick servicesector. The focus lies on convenient prices, which according to KNOTEK (2011) simplifies the purchase due to a lower number of necessary monetary units. Convenient prices that match round prices ending on monetary denominations prevail. The only exceptions are fast-food-restaurants, which offered often odd prices. Consequently, in these stores at least one monetary unit more than in takeaway shops would be necessary to pay for the products. The study shows that there are common principles in pricing strategies in the quick service sector and the retailing sector, but also differences.
Keywords: 330; Fast Food; Konsumentenverhalten; Einzelhandelspreis; Schnellgastronomie